Application study of multidisciplinary collaboration (MDT) integrated management model in perioperative management of patients with infectious nonunion - Lu, Qing; Bi, Zhaodong; Tian, Yunxu; Li, Yuqing; Zhang, Shanshan; Li, Xiuting; Xing, Wenzhao (Frontiers in Surgery, 2024)
Objective To explore the effectiveness of a multidisciplinary treatment (MDT) integrated intervention model in the perioperative management of patients with infectious nonunion. Methods 80 patients with infectious bone defects treated in our hospital from January 2020 to January 2023 were selected. They were classified into MDT-integrated perioperative group (study group) and conventional control group according to the different management patterns, with 40 cases each. The incidence of wound infection, pin tract infection, delayed bone healing, deep vein thrombosis (DVT), joint stiffness, and nutritional indicators were compared between the two groups. Results The rates of wound infection (P = 0.042), pin tract infection of Grade II or above (P = 0.006), delayed bone healing (P = 0.006), DVT (P = 0.033), and joint stiffness (P = 0.023) in the MDT integrated perioperative (study) group were significantly lower than those in the conventional care group (P < 0.05). With the extension of intervention time, the changes in body weight, levels of serum albumin (ALB), pre-albumin (PA), hemoglobin (Hb), and serum sodium (Na) in the study group were higher than those in the conventional care group (P < 0.05). Conclusion The application of the MDT integrated intervention model in the perioperative period of patients with infectious nonunion is beneficial in reducing the risks of wound infection and pin tract infection of Grade II or above, lowering the incidence rates of lower limb DVT and joint stiffness, and reducing the risk of malnutrition, demonstrating high clinical application value.